Democratic Paradoxes: Thomas Hill Green on Democracy and Education - Nesbitt, Darin R.; Trott, Elizabeth (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
This paper provides an account of the paradoxes of teaching democracy, the paradoxes of being a citizen in a liberal democracy, and the insights that can be gained from the model of citizenship that T.H. Green promoted. Green thought citizenship was predicated on the twin foundations of the community and the common good. Freedom for Green means individual self-determination coupled with recognition of the dependency relations between individuals and the community. Green is noteworthy not only as a theorist but also as an active contributor to the development of public schools in England. A consideration of his arguments provides a model for educating citizens, addresses the paradoxes of democracy in education, and reveals elements of his philosophy that are relevant to educational issues today.